Babukhadiya K.R., Reshetnik E.I. Functional cottage cheese product enriched with non-traditional vegetable components - A. O. Ermolaev; K. R. Babukhadiya; E. I. Reshetnik (Новые технологии, 2021)
The article considers the possibility of expanding the range of fermented milk products enriched with natural sources of biologically active substances, which is an urgent task today, as it corresponds to the concept of state policy of the Russian Federation in the field of healthy nutrition. As a solution to this problem, it has proposed to enrich the curd mass as part of the daily diet. Promising plant raw materials of the Far Eastern region, such as Ahnfeltia tobuchinensis, a representative of the genus of red algae growing in the Far Eastern Seas, are used as functional and enriching ingredients; Dahurian larch wood extract – arabinogalactan (Lavitol-arabinogalactan) and peppermint (Méntha piperíta). Grounded ahnfeltia was used in the size of not more than 0,5 mm. On the basis of the analysis of the composition and properties of the applied non-traditional additives, the possibility of enrichment of curd products with dietary fiber and organic iodine from plant components has been substantiated. Optimal ratios of enriching prescription components to the weight of cottage cheese in a finished product are the following: ahnfeltia powder – 1,5%, arabinogalactan – 2,5%, peppermint – 1%. Also, when determining the optimal dosages of the introduced components, it is proposed to replace the prescription amount of sugar with flower honey, which is a natural sweetener and a powerful antioxidant. Organoleptic and physicochemical parameters of the finished samples have been analyzed. As a result of the research the functional curd product one portion (100 g) of which is capable to satisfy daily physiological need of an organism for iodine for 29,32%, in dietary fibers for 12,38% has been developed.